1996
DOI: 10.1002/(sici)1097-4660(199604)65:4<343::aid-jctb461>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Culture pH and Aeration on Ethanol Production and Pullulan Molecular Weight by Aureobasidium pullulans

Abstract: The formation of ethanol by the polymorphic fungus Aureobasidium pullulans was examined under a range of culture pH values and aeration conditions. Although culture pH had a profound effect on fungal morphology, with a greatly increased proportion of the biomass in the unicellular (yeast-like) form at pH 6.5, there appeared to be no direct link between morphological form and ethanol formation. The levels of ethanol noted may have influenced the morphology. Cessation of aeration rapidly led to a halt in growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…The effects of carbon source (Mohammad et al, 1995;Madi et al, 1996), shear stress, agitation, aeration and dissolved oxygen levels Seviour, 1996, 1998), production enhancers (such as zinc and iron (Reeslev and Jensen, 1995)), and cell morphology (Ronen et al, 2002), have been studied to improve the production of high molecular weight, pure, and viscous pullulan. More statistically significant evaluations among these fermentation parameters have also been investigated by using response surface methodology (Goksungur et al, 2005;Urkut et al, 2007).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The effects of carbon source (Mohammad et al, 1995;Madi et al, 1996), shear stress, agitation, aeration and dissolved oxygen levels Seviour, 1996, 1998), production enhancers (such as zinc and iron (Reeslev and Jensen, 1995)), and cell morphology (Ronen et al, 2002), have been studied to improve the production of high molecular weight, pure, and viscous pullulan. More statistically significant evaluations among these fermentation parameters have also been investigated by using response surface methodology (Goksungur et al, 2005;Urkut et al, 2007).…”
Section: Introductionsupporting
confidence: 68%
“…Environmental pH, for example, plays a significant role on pullulan production (Shingel, 2004). Relatively low pH suppresses the synthesis of pullulan, but stimulates the reproduction of fungi (Catley, 1971;Seviour et al, 1992;Madi et al, 1996). Lacroix et al (1985) reported that A. pullulans can accumulate biomass first at low pH (i.e., 2.0) and began to produce pullulan after pH was adjusted to higher value.…”
Section: Introductionmentioning
confidence: 99%
“…Superior performance seen with the marine propeller may also be associated with reduced local shear rates and better gross circulation throughout the fermenter. Madi et al (1996) reported that aeration was necessary for cell growth and pullulan synthesis and observed a similar decrease in DO, followed by a rise to near saturation at which point production of EPS and biomass ceased. Here, high DO levels with the Rushton impellers correlated with greater biomass but lower EPS production, compared to results with the marine propeller.…”
Section: Resultsmentioning
confidence: 88%
“…Published accounts of pullulan production have focused on the effect of carbon and energy source (Mohamed et al, 1995A and1995B;Shabtai and Mukmenev, 1995;Israilides et al, 1998), effect of nitrogen availability (Catley, 1973), effect of pH (Ono et al, 1977), effect of shear stress and dissolved oxygen levels Seviour, 1996, 1998), effect of zinc and iron (Reeslev and Jensen, 1995), effect of cell morphology (Simon et al, 1993(Simon et al, , 1995(Simon et al, , 1998, effect of pH and aeration on production of ethanol and molecular weight of produced pullulan (Madi et al, 1996), comparison of stirred tank batch and fed-batch fermentations (Youssef et al, 1999), and use of glucosamine as the carbon and energy source to improve production of high molecular weight pullulan (Kim et al, 2000). This paper compares pullulan production by five strains of A. pullulans under similar fermentation conditions and also shows how culture conditions and experimental protocol influence pigment formation and the molecular weight, yield, and titer of this watersoluble polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing these fermentation results with those from a stirred tank fermenter, 13 on the same basis of pH, substrate, air flow rate, etc, Fig 6 suggests that the OBB produced higher polysaccharide and biomass levels in both types of fermentations than the STR and more efficiently, ie it took less than half the time to achieve a similar level of polysaccharide/biomass in the OBB than in the STR. As the OBB offers a more uniform mixing environment for cell growth and excellent mass transfer characteristics with respect to substrate, product and oxygen, this led to a sufficient supply of carbohydrates and other nutrients to the cells, and efficient removal of gases and other byproduct of catabolism from the microenvironment of the cells.…”
Section: Comparison With Strmentioning
confidence: 94%